Singapore's big gamble : the integrated resorts five years on - Toh, Andrew Yong Ren (2015)
No other subject has so inflamed the passions of Singaporeans as the integrated resorts (IR). First proposed in 2004 by then Minister for Trade and Industry George Yeo, the subject immediately drew a maelstrom of views from the public. Five years on, it seems the worst fears have been misplaced. Opening their doors to the public just as the global economy was gathering pace after the 2008 financial crisis, the resorts helped Singapore’s economy roar back from where it had languished, far ahead of the recovery in neighbouring countries in the region. But along with the blistering financial and economic results came more sobering news. Numerous support groups have reported seeing a rise in the number of people seeking treatment for gambling addiction. As the country grapples with the repercussions of the resorts, both good and bad, questions have been raised about whether the integrated resorts have delivered as much as the government has promised. Those questions are still being asked today.